Design of the medicines storage area in hospital wards. Issue 2 (12th March 2012) - Gil, I.; Font, I.; Bernabé, J.; Edo, M.; Bosó, V.; Poveda, J.L.
Abstract : Background: It is important to know the preferences of the users on the design of the medicines storage area to optimise resources and avoid errors that reach the patient. Purpose: To find out the preferences of the chief nurses on the design and functioning of the medicines storage area in hospital wards Materials and methods: The authors interviewed 25 chief nurses from May to June of 2011. They were asked to name the most important characteristics that a medicines storage area needs to have. Then they had to rate them (1 to 10) according to the importance. Results: A total of 15 specifications were grouped in 4 categories: Classification, Stock and replacement, Safety and Structure. The most requested specifications were the following: 1.-Medicines arranged in alphabetical order (9.37, Classification) 2.-Medicines included and stocks suitable for the needs of the hospital ward and daily replacements (9.36, Stock and replacement). 3.- Medicines containers should be labelled with the name of the drug and the trade name (9.25, Safety). 4.- Big and legible labels (9.10, Safety). 5.- Medicines classified by route of administration (9.02, Classification). 6.- Medicines storage area located near the nurses' work station (8.94, Structure). 7.-Visual code (symbols or colours) on the label to indicate the medicines close to expiry, route of administration, storage conditions, high risk medicines, etc. (8.75, Safety). 8.- The logistics department should provide daily information about replacing the medicines and the reasons for the lack of medicines (8.67, Stock and reinstatement). 9.- More versatile medicines containers (8.46, Structure) 10.-Logistics department should review the expiry date of the medicines every three months (8.00, Stock and reinstatement). Conclusions: The safety dimension was the most valued. The most frequently mentioned categories were safety and structure.